Analisis Pemanfaatan Hasil Asesmen Diagnostik Kognitif dalam Perancangan Modul Ajar Berdiferensiasi di Kelas IV SD Negeri 2 Bakan, Lombok Tengah, NTB - Putri Azzahrawaani (Journal of Elementary Education Research, 2026)
The implementation of the Kurikulum Merdeka at SD Negeri 2 Bakan requires a paradigm shift in lesson planning, moving from a "one-size-fits-all" approach to differentiated instruction. Central to this shift is the effective use of cognitive diagnostic assessments to map students' diverse learning readiness.This study aims to analyze the process and impact of utilizing cognitive diagnostic assessment results in designing differentiated teaching modules (Modul Ajar) for fourth-grade students.This research employs a qualitative descriptive method with a case study approach. The subjects are the fourth-grade teacher and students at SD Negeri 2 Bakan. Data were collected through deep interviews, classroom observations, and documentation analysis of diagnostic results and teaching modules. Data validity was ensured through source and technique triangulation.The findings indicate that diagnostic results allow for three types of differentiation: content, process, and product. By understanding students' initial cognitive levels, teachers could design role-play and discourse analysis activities tailored to students' sociocultural backgrounds. Integrating diagnostic data into differentiated modules bridges the gap between students' initial abilities and the required communicative competencies, fostering a more inclusive and effective learning environment.